2016
DOI: 10.1051/epjap/2016150537
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma deposition of antimicrobial coatings on non-woven textiles

Abstract: Abstract.A simple method for preparation of nanoparticle incorporated non-woven fabric with high antibacterial efficiency has been proposed based on atmospheric pressure plasma process. In this work direct current plasma jet stabilized by fast nitrogen flow was used as a plasma deposition source. Three different types of the nanoparticles (silver, copper and zinc oxide nanoparticles) were employed as antimicrobial agents. X-ray photoelectron spectroscopy (XPS) measurements have shown a positive chemical shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A possible explanation of the cracks formation can be ascribed to the higher discharge temperature when water droplets (and water vapor) were introduced in the discharge [ 42 ] indeed thermal stress of the deposited coatings and treated substrates could have induced crack and defect production [ 43 ]. Even if defects of plasma coating deposition are usually undesired [ 44 , 45 ] Nikiforov et al [ 46 , 47 ] reported on the key role of cracks for the delivery of silver ions from nanostructured films deposited on non-woven fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation of the cracks formation can be ascribed to the higher discharge temperature when water droplets (and water vapor) were introduced in the discharge [ 42 ] indeed thermal stress of the deposited coatings and treated substrates could have induced crack and defect production [ 43 ]. Even if defects of plasma coating deposition are usually undesired [ 44 , 45 ] Nikiforov et al [ 46 , 47 ] reported on the key role of cracks for the delivery of silver ions from nanostructured films deposited on non-woven fabrics.…”
Section: Resultsmentioning
confidence: 99%
“…After detailed and careful optimization of the process parameters (monomer and crosslinker content, plasma treatment time, discharge power), hydrophobic coatings with good washing durability were obtained. Nikiforov et al 156 used an APP deposition process of HMDSO to deposit a thin organosilicon film on PET fabrics in order to enhance subsequent deposition and adhesion of silver, copper, and zinc oxide nanoparticles (NPs). Initial deposition of organosilicon film using N 2 with a small amount of O 2 onto the PET surface was followed by immersion in a dispersion of NPs in ethanol.…”
Section: Coating and Polymerization Processesmentioning
confidence: 99%
“…Fahmy et al and Cruz et al attached silver NPs on a surface by using plasma polymerization of allyl alcohol and polymethylmethacrylate respectively, followed by incorporation of silver NPs on top of the plasma polymerized layer [38,39]. The reversed order process, deposition of a thin layer of plasma on top of silver NPs to improve adhesion, has not been extensively explored [40]. This is probably because direct contact from silver NPs, which not probable from below a conformal coating, is usually considered to be a requirement for antibacterial effect, as demonstrated in literature [41].…”
Section: Accepted Manuscriptmentioning
confidence: 99%